Social Reintegration Model for Juvenile Prisoners: An Indonesian Perspective - Kasmanto Rinaldi (Faculty of Law Universitas Jenderal Soedirman, 2024)
This study explores the coaching model applied to juvenile recidivist juveniles in Pekanbaru to achieve successful social reintegration. Using a qualitative approach through interviews, observation, and documentation, coupled with relying on the Nvivo 12 Plus analysis tool for data coding, this study deeply understood the model of fostering juvenile recidivists. The research findings show that the coaching model for recidivists in Pekanbaru includes rehabilitation, education and skills approaches, social support, reintegration into society, supervision and monitoring, strengthening the youth justice system, and education about law and consequences. It is effective in helping children improve themselves and avoid criminal behaviour. A holistic approach focusing on understanding the causes of problems, empowerment, and positive social support is the key to their successful social reintegration.